2014
DOI: 10.1177/0194599814541627a234
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and Surgeon Adherence to Pediatric Tonsillectomy Guidelines Regarding Perioperative Dexamethasone and Antibiotic Administration

Abstract: Objectives: Evaluate change in true vocal fold length as function of age.Methods: Prospective study at tertiary aerodigestive center between 2011 and 2013. A total of 205 patients (ages 1 month to 20 years), of which 87 (42.4%) were female and 118 (57.6%) male, were included. Lengths of total vocal fold (TVFL), membranous vocal fold (MVFL), and cartilaginous vocal fold (CVFL) were measured during direct laryngoscopy. Membranousto-cartilaginous ratios (M/C) were calculated.Results: Mean MVFL under age 1 year fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…Our results indicate that while most surgeons did not prescribe any antibiotics for tonsillectomy ± adenoidectomy, a significant number prescribe post-operative antibiotics. Our findings were similar to previous studies in the USA where 30-40% of surgeons surveyed, prescribe antibiotics for these operations (10,12). Common reasons for prescribing antibiotics in this survey were prevention of infection, less post-operative pain and less post-operative bleeding.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results indicate that while most surgeons did not prescribe any antibiotics for tonsillectomy ± adenoidectomy, a significant number prescribe post-operative antibiotics. Our findings were similar to previous studies in the USA where 30-40% of surgeons surveyed, prescribe antibiotics for these operations (10,12). Common reasons for prescribing antibiotics in this survey were prevention of infection, less post-operative pain and less post-operative bleeding.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, this study highlights a gap between current guidelines and prescribing practices in some areas of Otolaryngology Head and Neck Surgery. Although evidence in Australia and New Zealand on adherence to guidelines is sparse, previous studies in the Netherlands and USA have emphasised a need for increased awareness and implementation of guidelines in the future (9,10). Furthermore, the Australian Commission on Safety and Quality in Health Care have highlighted the need for increased collaboration with the Royal Australasian College of Surgeons to improve this gap (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…189 In addition, multiple studies have shown no significant change in pain, emergency room encounters, or hospitalization. 29,[190][191][192][193][194] Any real or theoretical benefit of antibiotics on recovery after tonsillectomy must be balanced against the known risks, harms, and adverse events of therapy. 195 Aside from the direct costs of acquiring the medications, adverse events include rash, allergy, and gastrointestinal upset or diarrhea.…”
Section: Supporting Textmentioning
confidence: 99%
“…Table 3 provides examples of research publications using different types of administrative data. -Centers for Medicare and Medicaid Services (CMS): MedPar, 69,70 state inpatient databases (SID), 35,52,[71][72][73] Medicaid Analytical eXtract (MAX), 74 Truven Health MarketScan® Multi-State Medicaid Database 75 -TRICARE 76 -University HealthSystem Consortium (UHC) 49 -Kids' Inpatient Database (KID) 77 -Pediatric Health Information System (PHIS) 47 -Premier Perspective 78,79 -Private insurers 11,12 85 -Individual health systems/ consortiums 9,12,23,27,28,37,[86][87][88][89] Surveillance, laboratory, or registry data -Defined as systematic collection of data for a clearly stated purpose -Can include both administrative and clinical data -Programs may allow multiple institutions to pool deidentified data for a common study.…”
Section: Pitfalls and Tipsmentioning
confidence: 99%